Voluntary Associations and Political Culture in Post-Gadhafi Libya - Romanet Perroux, Jean-Louis. (2017)
Abstract: In 2011, a popular revolution in Libya brought about the collapse of a brutal regime, the disintegration of state institutions that were already historically weak, and the dislocation of society and traditions. At the same time, thousands of Libyans formed voluntary associations of all kinds throughout Libya, and continue to do so notwithstanding these highly unfavorable circumstances. However, these associations do not necessarily constitute a civil society - one that promotes civic values such as pluralism, equality, and tolerance. Libyans had not experienced free associational life since the mid-seventies; they lacked a culture of public participation; they were plagued by violence and lawlessness; and they were stripped of institutions capable of promoting and protecting civic engagement. Overall, the social, economic and political conditions that characterize Libyan history and the post-Gadhafi environment are not propitious for the development of a voluntary associational sector that possesses a civic political culture. In light of these premises, to what extent do Libyan voluntary associations embody and express a civic political culture (e.g. trust, tolerance, religious openness, support for gender equality, political engagement) in comparison to the civic attitudes and political behaviors that prevail among Libyans? And what explains the emergence of this civil society in such a violent and lawless environment? Through the analysis of the data drawn from three independent surveys conducted across the country between 2012 and 2014, I present a strong and convincing body of empirical evidence, which shows that voluntary associations embody and express a civic political culture. Moreover, on the basis of an in-depth inquiry through dozens of individual stories of civil society activists and organizations I identify two avenues that help to explain the development of a civic culture and a strong civil society in unfavorable settings. The first is a process of exposure to foreign information, behaviors and meanings that represent one facet of the phenomenon known as globalization. It is driven by traveling, reading, connections to a diaspora, access to satellite television, the internet, and to other forms of foreign information. The second is the novel availability of a quasi-public space constituted by interactive communication platforms available through the internet, and "smart" mobile phones.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Katrina Burgess.; Committee: Zeynep Bulutgil, Melani Cammett, and Shai Feldman.; Keywords: International relations, Sociology, and Political science.